2014
DOI: 10.1016/j.jacc.2013.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Local Stiffness of the Carotid and Femoral Artery Is Associated With Incident Cardiovascular Events and All-Cause Mortality

Abstract: Carotid and femoral stiffness indices are independently associated with incident cardiovascular events and all-cause mortality. The strength of these associations with events may differ per stiffness parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
4
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(211 citation statements)
references
References 28 publications
11
189
4
7
Order By: Relevance
“…Arterial stiffness is not uniform along the arterial tree; therefore, assessment of arterial stiffness at different sites in relation to clinical outcomes is important (29). We have previously shown that arterial stiffness measured as carotid femoral PWV is associated with cardiovascular morbidity and mortality; however, we did not observe such an association with stiffness in the carotid artery.…”
Section: Discussioncontrasting
confidence: 69%
“…Arterial stiffness is not uniform along the arterial tree; therefore, assessment of arterial stiffness at different sites in relation to clinical outcomes is important (29). We have previously shown that arterial stiffness measured as carotid femoral PWV is associated with cardiovascular morbidity and mortality; however, we did not observe such an association with stiffness in the carotid artery.…”
Section: Discussioncontrasting
confidence: 69%
“…For this reason, there has been large interest in methods for the assessment of arterial stiffness, a potentially potent biomarker of cardiovascular disease with demonstrated prognostic ability [3][4][5][6]. In the clinical setting, arterial stiffness is most commonly derived by measuring the pulse wave velocity (i.e., the speed with which the arterial pulse travels along the arterial segment) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…19 It was also hypothesized that modification of arterial stiffness may influence future CV events. Studies performed so far have reported conflicting results on the effect of antihypertensive treatment on arterial stiffness.…”
Section: -17mentioning
confidence: 99%